2021
DOI: 10.1080/14760584.2021.1886930
|View full text |Cite
|
Sign up to set email alerts
|

Latin American forum on immunization services during the COVID-19 pandemic

Abstract: Introduction: The Latin American Society of Pediatric Infectology (SLIPE for its acronym in Spanish) is working hard to contribute with strategic actions to prevent the recurrence of Vaccine-Preventable Diseases and to prevent the reduction of vaccine coverage in the region of the Americas. Areas covered: On Friday, September 25th, a Latin American forum of experts on immunization services during the COVID-19 pandemic was held through Webex platform. Issues such as: the imminent risk of occurrence and outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…The systematic literature review included 14 studies out of 696 publications identified through the five databases ( Figure 2 ). 13–15 , 20–30 A description of the main characteristics of the studies follows; further details are presented in Table S4.
Figure 2.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic literature review included 14 studies out of 696 publications identified through the five databases ( Figure 2 ). 13–15 , 20–30 A description of the main characteristics of the studies follows; further details are presented in Table S4.
Figure 2.
…”
Section: Resultsmentioning
confidence: 99%
“…Geographically, the included studies presented nationwide (n = 6), 20–21 , 26–29 regional (n = 4) 13 , 15 , 24 , 25 or international (n = 4) 14 , 22 , 23 , 30 data (Figure S1). Among the studies reporting nationwide data, the highest number reported data from Brazil (n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing inequalities in routine immunizations and subnational coverage gaps in LAC have been deepened by the COVID-19 pandemic, particularly in light of the disproportionate impact of COVID-19 on vulnerable populations in the region as well as the long-standing inequalities in health service access and utilization [9] , [10] , [11] . The Access to COVID-19 Tools (ACT) Accelerator, a global collaboration launched by the WHO, provides leadership and integrated guidance in partnership with governments, private sector organizations, civil society, and philanthropic entities around the world to strengthen health systems and support the development, production, and equitable access to COVID-19 testing, treatment, and vaccines.…”
Section: Introductionmentioning
confidence: 99%